Validation of reference genes for normalization of qPCR mRNA expression levels in Staphylococcus aureus exposed to osmotic and lactic acid stress conditions encountered during food production and preservation. Issue 1 (19th June 2014) - Sihto, Henna‐Maria; Tasara, Taurai; Stephan, Roger; Johler, Sophia
Abstract Staphylococcus aureus represents the most prevalent cause of food‐borne intoxications worldwide. While being repressed by competing bacteria in most matrices, this pathogen exhibits crucial competitive advantages during growth at high salt concentrations or low pH, conditions frequently encountered in food production and preservation. We aimed to identify reference genes that could be used to normalize qPCR mRNA expression levels during growth of S. aureus in food‐related osmotic (NaCl) and acidic (lactic acid) stress adaptation models. Expression stability of nine housekeeping genes was evaluated in full (LB) and nutrient‐deficient (CYGP w/o glucose) medium under conditions of osmotic (4.5% NaCl) and acidic stress (lactic acid, pH 6.0) after 2‐h exposure. Among the set of candidate reference genes investigated, rplD, rpoB, gyrB, and rho were most stably expressed in LB and thus represent the most suitable reference genes for normalization of qPCR data in osmotic or lactic acid stress models in a rich medium. Under nutrient‐deficient conditions, expression of rho and rpoB was highly stable across all tested conditions. The presented comprehensive data on changes in expression of various S. aureus housekeeping genes under conditions of osmotic and lactic acid stress facilitate selection of reference genes for qPCR‐based stress response models.